Efektivitas Teknik Reframing Untuk Meningkatkan Kepercayaan Diri Melakukan Passing Bawah Permainan Bola Voli Pada Pembelajaran PJOK Kelas VII - Dini Uswatun Hasanah Dini; Jhony Hendra; Titis Wulandari (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2025)
This research is based on the lack of student confidence when making a low pass on volleyball. This study aims to see the effectiveness of reframing techniques to increase confidence in passing under volleyball in class VII PJOK learning. This research is an experimental research, where the research aims to increase confidence in passing down. In this study, data collection was carried out using pree test and post confidence test methods using questionnaires. The population of this study is all students of MTS Shaikh Daud Al Masrur as many as 77 students, the sampling technique uses purposive sampling as many as 24 students. The data that has been collected will be analyzed using paired tests with the help of IBM SPSS 20 at a significance level of 5%. The results of the study showed that the pre-test score of the student's confidence level had an average score of 65.50 in the "Sufficient" category while the results of the post test score increased to 122.38 in the "Very Good" category. With the results of the Shapiro-Wilk normality test, which is 0.002 >0.05, it means that the data is normally distributed, while the hypothesis results using the Wilcoxon signed test obtained a Z value of -4.288 and an asymp sig value. (2-tailed) 0.000 is smaller than the alpha level of 5% (0.05) so Ho is rejected and Ha is accepted, so the conclusion is that there is a difference. This is the effectiveness of reframing techniques to increase confidence in passing down volleyball games in class VII PJOK learning.